TOXINA BOTULÍNICA TIPO A COMO ADJUVANTE NO CONTROLE DA DOR PÓS-OPERATÓRIA EM CADELAS SUBMETIDAS À MASTECTOMIA - Vilhegas, Sérgio (2013)
The aim of this study was to evaluate the analgesic effects of botulinum toxin as an adjunct in the control of postoperative pain in dogs. In a blinded study, sixteen dogs undergoing mastectomy were randomly assigned to two groups of 08 animals each and received 7U kg-1 of botulinum toxin diluted in 10mL of saline and administered 1mL in each breast, subcutaneously (TXB) or 1mL of saline administered in each breast (Control), subcutaneously. After twenty four hours, pre-anesthetic medication was intramuscular (IM) acepromazine (0.03mg kg-1) in combination with morphine (0.3mg kg-1). Anesthesia was induced with intravenously (IV) propofol (4 to 5mg kg-1) and maintained with isoflurane. The analgesic intra-operative support was provided by IV continuous rate morphine (0.1mg kg-1h-1). Heart rate, respiratory rate, systolic arterial blood pressure, oxicapnografy and end-tidal concentration of isoflurane were evaluated during the surgery. Postoperative analgesia was assessed during the first 72 hours after the tracheal extubation using a Visual Analog Scale (VAS) and Glasgow Modified Scale (GMS). Rescue analgesia with morphine (0.5mg kg-1 IM) was performed if the evaluation score exceeded 50% of VAS and/or 30% of GMS during the postoperative period. The pain scores were lower in TXB group than in Control group from 8 to 60 hours and from 12 to 60 hours post-extubation, according to VAS and GMS scales, respectively. Postoperative rescue analgesia was lower in the TXB group (2 of 8 dogs), when compared with Control group (7 of 8 dogs). Cardiopulmonary established was detected in both treatment groups. Preemptive botulinum toxin administration is a satisfactory alternative to post-operative management in dogs undergoing mastectomy.